2007
DOI: 10.1177/1531003506298080
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Arteriography for Lower Extremity Revascularization

Abstract: Duplex arteriography may be a potential replacement of preoperative standard contrast arteriography for peripheral arterial imaging in lower extremity revascularization procedures. In patients with chronic or acute ischemia, a well-performed duplex arteriography offers several practical advantages over contrast arteriography: it is noninvasive; it does not require nephrotoxic agents; it is portable and can be done expeditiously; color flow and waveform analysis provide a better estimation of the hemodynamic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…Based on prior publications, our findings might even underestimate the potential of DUS for treatment planning, and the value of additional imaging might even be of less than found in this study. 3,12,[25][26][27] The variability in treatment planning and scoring behavior of reviewers is an important limitation of this study. This variability might partially be the result of our multinational study design and the fact that one reviewer's decisions were based on consensus, whereas others decided individually.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on prior publications, our findings might even underestimate the potential of DUS for treatment planning, and the value of additional imaging might even be of less than found in this study. 3,12,[25][26][27] The variability in treatment planning and scoring behavior of reviewers is an important limitation of this study. This variability might partially be the result of our multinational study design and the fact that one reviewer's decisions were based on consensus, whereas others decided individually.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other publications in this field, we highlight the need for internal validation of technicians, clinicians, and a close relationship between these 2 before adopting a workup with DUS only, because the utility of DUS is known to be dependent on the skills of technicians and confidence and trust of clinicians. 3 Future directions and recommendations. While recognizing variability between centers and clinicians, this study identified the obstacle of clinician confidence as a factor that could hamper greater use of DUS in the appropriate clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 For example, in many vascular centers, carotid endarterectomy, and lower-extremity arterial bypass is planned on the basis of duplex scanning alone, in most of their patients. 11,12 Duplex scanning has become the standard test for the evaluation of patients with suspected deep vein thrombosis. Decisions regarding anticoagulation therapy are typically made without resorting to invasive contrast studies such as venography.…”
Section: Introductionmentioning
confidence: 99%